Sonographic and radiographic findings in congenital renal dysplasia in a female Lhasa apso - Belotta, A. F.; Souza, P. M. [UNESP]; Machado, Vania Maria de Vasconcelos [UNESP]; Vulcano, Luiz Carlos [UNESP]; Bento, D. D. [UNESP]; Lourenço, Maria Lucia Gomes [UNESP]; Silva, M. L. C. da [UNESP]; Rocha, Noeme Sousa [UNESP] (Univ Federal Rural Pernambuco, 2011)
An 8-month-old Lhasa Apso female dog was referred to the Veterinary Hospital, FMVZ, Unesp, Botucatu Campus, with suspected congenital renal disorder. Ultrasound images revealed higher renal echogenicity, loss of corticomedullary demarcation and diverticular mineralization on the right kidney. The mucosal lining of the stomach was hyperechoic and radiographic examination demonstrated mineralization of wall and folds, which is consistent with uremic gastropathy.
Keywords: kidneys; dysplasia; imaging diagnosis